Lestiphorus bilunulatus yamatonis Tsuneki, 1963 (Hymenoptera, Crabronidae) raised to full species status, with description of the hitherto unknown male - Mokrousov, Mikhail V.; Proshchalykin, Maxim Yu. (Zootaxa, 2023)
Lestiphorus yamatonis Tsuneki, 1963, stat. nov. is resurrected from synonymy and raised to full species level. The species diagnosis is updated and the hitherto unknown male is described. Illustrations of morphological details of L. yamatonis and related species are given. An updated key of the all twelve Palaearctic Lestiphorus is provided.